2016
DOI: 10.1111/pace.12907
|View full text |Cite
|
Sign up to set email alerts
|

Atrial Fibrillation and Cardiovascular Outcomes in the Elderly

Abstract: AF is associated with several adverse cardiovascular outcomes and heart failure is the most frequently detected event. Potentially, risk factor modification strategies for the primary prevention of heart failure will reduce the morbidity and mortality associated with AF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
21
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 36 publications
3
21
0
Order By: Relevance
“…Beta‐blockers, especially beta‐1‐selective beta‐blockers, but also non‐selective beta‐blockers among men, were associated with a lower risk of incident CHF, but also in general with a lower mortality risk in heart diseases supporting our findings on CHF, as CHF is a great contributor to mortality in AF 7 . Studies on beta‐blockers in hypertension and the risk of CHF have shown conflicting results, with one review finding no positive effect, 12 and another a preventive effect 16 .…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Beta‐blockers, especially beta‐1‐selective beta‐blockers, but also non‐selective beta‐blockers among men, were associated with a lower risk of incident CHF, but also in general with a lower mortality risk in heart diseases supporting our findings on CHF, as CHF is a great contributor to mortality in AF 7 . Studies on beta‐blockers in hypertension and the risk of CHF have shown conflicting results, with one review finding no positive effect, 12 and another a preventive effect 16 .…”
Section: Discussionsupporting
confidence: 83%
“…Even if ischemic stroke is the most well‐known disease associated with AF, 5,6 congestive heart failure (CHF) is also of great importance and is three times more common in AF patients compared with non‐AF patients 7 . CHF and AF are interrelated diseases 8,9 with one that could precede the other.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior studies in the non-CKD population have also reported strong links between AF and HF. [6][7][8][9][10][11][12]44,45 Among participants in the Framingham study, AF was associated with a two-fold increased risk of incident HF, 46 and HF was the most common nonfatal CVD outcome after AF in Medicare beneficiaries. 14 Other studies in non-CKD cohorts have also noted an association between AF and risk of MI.…”
Section: Discussionmentioning
confidence: 99%
“…As regards gout in relation to ischemic stroke, hyperuricemia is shown to increase the risk of ischemic stroke [15], and add to predictive value to the most common clinical risk predictor of ischemic stroke in AF, i.e., the CHA 2 DS 2 -VASc [16]. However, there are also other risks with AF, with congestive heart failure (CHF) being more common among patients with AF compared to individuals without AF [17], and CHF is the most common cause of death among patients with AF [18]. AF is also associated with development of dementia [19].…”
Section: Introductionmentioning
confidence: 99%